The Clinical Evaluation Value of the NRF2-Mediated Antioxidant Stress Mechanism in Elderly Patients with Type 2 Diabetes Mellitus Complicated by Osteoporosis - Fulati, Reyila; Ailiyasi, Guzainu; Baihetiya, Renagu; Yu, JiWei; Wang, XiuFang; Li, ZhenHua; Tulake, Gulizhaer (Journal of Medical Biochemistry, 2025)
Objective: The role of nuclear factor erythroid 2-related factor 2 (NRF2) as a central transcription factor in the regulation of cellular antioxidant stress is of significant interest, particularly in its potential clinical relevance for elderly patients with type 2 diabetes mellitus (T2DM)-associated osteoporosis (T2DM-OP). Methods: A cohort of 196 patients with T2DM who received treatment were recruited and stratified into three groups according to T-scores derived from bone mineral density (BMD) assessments. Serum concentrations of 25-hydroxyvitamin D3, osteocalcin (OC), procollagen type I N-terminal propeptide (P1NP), β-isomerized C-terminal telopeptide of type I collagen (β-CTX), as well as nuclear factor erythroid 2-related factor 2 (NRF2), superoxide dismutase (SOD), and malondialdehyde (MDA) were quantified utilizing enzyme-linked immunosorbent assay techniques. Pearson correlation analysis was conducted to explore the relationships among NRF2, SOD, MDA, and BMD. Additionally, multivariate logistic regression analysis was employed to investigate the association between Asprosin levels and the risk of T2DM-OP. Results: There were no apparent differences in baseline characteristics (gender, age, BMI, duration of diabetes mellitus, and metabolic parameters) among the three groups (P > 0.05). Analysis revealed that lumbar spine BMD decreased evidently with declining bone mass (normal bone mass group 1.13 g/cm², osteopenia group 0.93 g/cm², osteoporosis group 0.80 g/cm², P < 0.001). In the osteoporosis cohort, there was a significant elevation in the bone resorption marker β-CTX and the bone formation marker OC (P < 0.001), indicating a pronounced imbalance in bone turnover. Among oxidative stress factors, SOD activity and NRF2 levels progressively decreased with bone loss, while MDA levels increased (all P < 0.001), indicating declined antioxidant capacity and aggravated oxidative damage. Correlation analysis showed that NRF2 and SOD were positively correlated with BMD, whereas MDA was negatively correlated with BMD. Multivariate logistic regression further confirmed that low NRF2, low SOD, and high MDA were independent risk factors for T2DM-OP (P < 0.05). Receiver operating characteristic curve analysis demonstrated that NRF2 exhibited high sensitivity (80.36%) and specificity (77.86%) in predicting T2DM-OP, with an area under the curve of 0.856 (95% CI: 0.803–0.909, P < 0.001), comparable to bone turnover indicators. Conclusion: The study reveals that the NRF2-mediated antioxidant response is crucial in the pathological progression of T2DM-OP, highlighting its potential as a new therapeutic target for prevention and treatment.